Criminal Responsibility of Child Intermediaries in Narcotics Trade Under Law No. 11/2012 on Juvenile Justice - Heliany, Ina; Windiyastuti, Feny; Said, Yusuf Muhamad (International Journal of Law Reconstruction, 2024)
The study aims to analyze the criminal responsibility of children who act as intermediaries in the sale and purchase of narcotics under Law No. 11 of 2012 concerning the child criminal justice system. Children involved in narcotics crimes are often exploited due to their vulnerability in understanding legal consequences. This research employs a normative juridical approach by examining legislation and relevant cases. The results indicate that while children can be subject to criminal sanctions, the child criminal justice system emphasizes rehabilitation and guidance efforts over imprisonment. The child criminal justice system provides special protection for children, prioritizing restorative justice, which seeks to restore the situation without focusing on punishment. However, challenges arise in implementing this system, particularly regarding the role of law enforcement officials and consistent application across Indonesia. This study recommends enhancing the understanding and capacity of law enforcers and strengthening the rehabilitation system for children involved in drug-related crimes.